2010
DOI: 10.1021/jm1004286
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of CP-690,550: A Potent and Selective Janus Kinase (JAK) Inhibitor for the Treatment of Autoimmune Diseases and Organ Transplant Rejection

Abstract: There is a critical need for safer and more convenient treatments for organ transplant rejection and autoimmune disorders such as rheumatoid arthritis. Janus tyrosine kinases (JAK1, JAK3) are expressed in lymphoid cells and are involved in the signaling of multiple cytokines important for various T cell functions. Blockade of the JAK1/JAK3-STAT pathway with a small molecule was anticipated to provide therapeutic immunosuppression/immunomodulation. The Pfizer compound library was screened against the catalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
236
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(255 citation statements)
references
References 36 publications
6
236
0
6
Order By: Relevance
“…These findings have potential therapeutic implications, as JAK kinase inhibitors are known to target these alterations. 15,[33][34][35][36][37][38] JAK3 is the most frequently mutated gene (16.1% of T-ALL cases) within the IL7R-JAK signaling pathway. Based on the results described in this article and our previously published work, 15 the transforming capacities of a total of 16 JAK3 mutants have been tested using the Ba/F3 in vitro cell system.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have potential therapeutic implications, as JAK kinase inhibitors are known to target these alterations. 15,[33][34][35][36][37][38] JAK3 is the most frequently mutated gene (16.1% of T-ALL cases) within the IL7R-JAK signaling pathway. Based on the results described in this article and our previously published work, 15 the transforming capacities of a total of 16 JAK3 mutants have been tested using the Ba/F3 in vitro cell system.…”
Section: Discussionmentioning
confidence: 99%
“…Tofacitinib, inhibitor of JAK3 was developed recently [257], but various clinical efficacies have been experienced. A multicentre, double-blind, placebo controlled study with tofacitinib in patients with moderate to severe active CD showed no clinically significant response following 4 weeks of treatment compared with placebo, but in patients with moderate to severe UC it showed improvement in both clinical response and remission rates [258,259].…”
Section: New Avenues Against Pro-inflammatory Cytokines or Downstreammentioning
confidence: 99%
“…[6 ] The drug inhibits signaling through JAK1 and JAK3 /STATpathway with selectively reduced cellular potency of JAK2. [7]Tofacitinib inhibits signaling by heterodimeric receptors bound among JAK1 and JAK3 with functional selectivity of receptors that signal via JAK2, which blocks signaling for several cytokines and interleukins.…”
Section: Mechanism Of Actionmentioning
confidence: 99%